New technologies in promotional televisual discourse (Comunicação & Inovação, 2016)
These days, Brazilian television, besides its private character and thus the need to submit to the restrictions of the market, has been living with fast technological growth, which means completely rethinking their duties and even share its audience time with phones, tablets, computers. In this sense, the objective of this study is to investigate the relationship between this media and the new technological devices available, analyzing their effects on specificity of televisual discourse production, especially that of promotional nature. Therefore, discusses the properties of the television in the country, the influence of economic and technological factors in the discursive production and seeks to examine these traces in a station's program (television series Sete vidas).
Keywords: Televisual media. Promotional discourse. New technologies. Discursive production. Expantion and condensation.